Efficient methane dry reforming process with low nickel loading for greenhouse gas mitigation - Pham, Cham Q.; Alsaiari, Mabkhoot A.; Hieu, Nguyen Huu; Pham, Thuy Phuong Thi; Le Phuong, Duy Ha; Natarajan, Rajamohan; Herma Dina, Setiabudi; Vo, Dai Viet Nguyen; Trinh, Thanh H.; Pham, Phuong Thi Hong; Nguyen, Tung Manh (Springer, 2023)
In this study, a series of nickels supported on gamma alumina with a metal dosage ranging from 0.5 to 3 wt.% were prepared and employed as the catalysts. The effect of nickel dosage on material properties, reaction performance, and catalyst deactivation was investigated. At a low dosage, the nickel-free having low metal-support interaction contributed significantly to the total active site. The basicity of the material was enhanced along with the increase in nickel loading. The presence of active metal showed a great impact at the beginning leading to big improvements in feedstock conversion. However, beyond a nickel dosage of 2 wt.%, further additions did not noticeably influence the reaction performance. Regarding catalyst deactivation, different carbon species were observed on catalyst surface, depending on the nickel dosage. Catalysts with less than 2 wt.% nickel exhibited amorphous carbon as the dominant morphology on the spent catalyst. In contrast, catalysts with 2Ni/Al2O3 and 3Ni/Al2O3 compositions showed graphitic carbon as the main side product. These findings provide insights into the relationship between nickel dosage, catalyst properties, and catalytic performance in methane dry reforming. By understanding the effects of nickel loading on material properties and reaction behavior, researchers can optimize catalyst design and develop more efficient and stable catalysts for sustainable syngas production.